Postcard from Georg Bredig to Max Bredig, June 6, 1937 - Bredig, Georg (1937)
Georg Bredig (1868-1944) informs his son, Max Albert Bredig (1902-1977) that a package was sent to him with bound volumes.
Keywords: Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Third Reich